Expression of inducible nitric oxide synthase, caspase-3 and production of reactive oxygen intermediate on endothelial cells culture (HUVECs) treated with P. falciparum infected erythrocytes and tumour necrosis factor-Î± (Medical Journal of Indonesia, 2006)
Cytoadherence of P. falciparum infected erythrocytes on endothelial cells is a key factor in development of severe malaria. This process may associated with the activation of local immune that was enhanced by tumour necrosis factor-Î± (TNF-Î±). This study was conducted to see the influence of P.falciparum infected erythrocytes cytoadherence and TNF-Î± treatment in inducing endothelial cells activation in vitro. inducible nitric oxide synthase (iNOS) and caspase-3 expression, also reactive oxygen intermediate (ROI) production were used as parameters. An Experimental laboratory study had been done to observe endothelial cells activation (HUVECs) after treatment with TNF-Î± for 20 hours or P. falciparum infected erythrocytes for 1 hour or both of them. Normal endothelial cells culture had been used as a control. Using immunocytochemistry local immune activation of endothelial cells was determined by iNOS and caspase-3 expression. Nitro Blue Tetrazolium reduction-assay was conducted to see the ROI production semi quantitatively. inducible nitric oxide synthase expression only found on endothelial cells culture treated with P. falciparum infected erythrocytes or both P. falciparum infected erythrocytes and TNF-Î±. Caspase-3 expression found slightly on normal endothelial cells culture. This expression increased significantly on endothelial cells culture treated with both P.falciparum infected erythrocytes and TNF-Î± (p=0.000). The normal endothelial cells release low level of ROI in the presence of non-specific trigger, PMA. In the presence of P. falciparum infected erythrocytes or TNF-Î± or both of them, some cells showed medium to high levels of ROI. Cytoadherence of P. falciparum infected erythrocytes and TNF Î± treatment on endothelial cells can induce activation of local immune marked by increase inducible nitric oxide synthase and release of free radicals that cause cell damage. (Med J Indones 2006; 15:151-6) Keywords: P.falciparum ,HUVECs, TNF-Î±, iNOS, Caspase-3, ROI